SISTEM PEMANTAUAN PADA PROTOTIPE BOILER MENGGUNAKAN HUMAN MACHINE INTERFACE CIMON - -, Jiordanus; Mamesah, Chrestian Maxi (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
In the energy industry, effective monitoring of boiler systems is crucial for ensuring safe and efficient operations. This study aims to implement a monitoring system on a boiler prototype using CIMON Human Machine Interface technology. The system is designed to monitor various operational parameters of the boiler, such as pressure, temperature, and flow, in real-time. By utilizing CIMON Human Machine Interface, data from the boiler's sensors are visually displayed through an intuitive graphical interface, allowing operators to monitor system performance more easily and quickly. The implementation also includes setting up alarms and notifications to detect abnormal conditions that could impact the safety and efficiency of the boiler. The results of this study indicate that the application of CIMON Human Machine Interface enhances the monitoring and control capabilities of the boiler and facilitates data management and response to potential issues. This research provides significant contributions to improving the reliability and effectiveness of boiler monitoring systems in industrial settings.